Soviet Views on Keynes: A Review Article Surveying the Literature - Letiche, John M. (Journal of Economic Literature, 1971)
In writing this paper I benefited greatly from information provided by visiting scholars (at Berkeley) from the Soviet Union, Hungary, Czechoslovakia, Poland, and Yugoslavia. To them, and to the following friends and colleagues, I am deeply indebted not only for stimulating discussions and research cooperation but also for observations based on personal experience-particularly on issues of fundamental disagreement: Carlo M. Cipolla, Gerard Debreu, Howard S. Ellis, Oldrich Kyn, Abba P. Lerner, Mark Perlman, Richard Roehl, and Benjamin Ward.